The variability of the Polish word stress. Oxytonesis - Osowicka-Kondratowicz, Magdalena (Papers in Linguistics, 2022)
The article is the second part of a study on the stress variability in Polish. The text presents the results of research on the phonetic awareness of young Poles regarding the evaluation of sound variants of selected accent doublets and applies to words with a normative stress on the last syllable, such as etui/etui, eksmąż/eksmąż etc. The proposed conclusions point to a relatively good auditory discrimination of phonetic variants of the words in question as well as differences between some of the respondents’ decisions regarding the correctness recommendations formulated in dictionaries.